2001
DOI: 10.1111/j.1949-8594.2001.tb18028.x
|View full text |Cite
|
Sign up to set email alerts
|

Reviewing Integrated Science and Mathematics: The Search for Evidence and Definitions From New Perspectives

Abstract: Based upon current research needs indicated from recent literature reviews, this integrative review concentrates on two of the perceived major impediments to integrating science and mathematics: The lack of evidence to support integration and the lack of a definition for integration. Using mixed methodology, this review found quantitative evidence favoring integration from a meta‐analysis of 31 studies of student achievement, qualitative evidence revealing the existence of multiple forms of integration, and hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
0
14

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(108 citation statements)
references
References 27 publications
2
92
0
14
Order By: Relevance
“…Using mixed methodology, Hurley's (2001) review addressed some of these issues and 'found quantitative evidence favoring integration from a meta-analysis of 31 studies of student achievement, qualitative evidence revealing the existence of multiple forms of integration, and historical evidence of publishing patterns from across the 20th century' (p. 259). Their analysis of 31 studies reported positive effect sizes of five distinct 'forms' of integration on learning outcomes in mathematics and science, with highest effects being 'sequenced (on maths)' and 'enhanced (on science)'.…”
Section: Review Of Reviewsmentioning
confidence: 99%
“…Using mixed methodology, Hurley's (2001) review addressed some of these issues and 'found quantitative evidence favoring integration from a meta-analysis of 31 studies of student achievement, qualitative evidence revealing the existence of multiple forms of integration, and historical evidence of publishing patterns from across the 20th century' (p. 259). Their analysis of 31 studies reported positive effect sizes of five distinct 'forms' of integration on learning outcomes in mathematics and science, with highest effects being 'sequenced (on maths)' and 'enhanced (on science)'.…”
Section: Review Of Reviewsmentioning
confidence: 99%
“…Çalışmaların ortak bulgusu olarak, fen ve matematik entegrasyonunun öğrencilerin başarısını (Hurley, 2001;Kıray ve Kaptan, 2012), motivasyon ve problem çözme yeteneklerini etkilediği (Offer ve Vasquez-Mireless, 1999;Venville ve diğerleri, 2004) rapor edilmiştir. Çetin ve arkadaşları (2015) öğrencilerin fen ve matematik başarıları arasında güçlü bir ilişki olduğu sonucuna varmışlardır.…”
Section: Geni̇şleti̇lmi̇ş öZetunclassified
“…Integration of disciplines such as science, mathematics and technology in teaching has long been aimed to deepen students' understanding by conceptualizing as well as broaden students' understanding (Czerniak, 2007;Roehrig, Moore, Wang & Park, 2012;Wang, 2005). As a common finding, studies indicated that integration of science and mathematics enhance students' achievement (e.g., Hurley, 2001;Kiray & Kaptan, 2012;Wang, 2005) as well as students' motivation and problem solving skills (Offer & Vasquez-Mireless, 1999) and helps students to make abstract concepts more concrete by using multiple representations (e.g. pictures, tables and graphs).…”
Section: Introductionmentioning
confidence: 99%
“…Ailleurs, et du côté de la recherche, la question des liens unissant les disciplines sciences et mathématiques ou de l'intégration des matières selon certains, est à la fois ancienne et contemporaine (Bassok et Holyoak, 1989;Hurley, 2001;Malafosse, Lerouge et Dusseau, 2001;Maloney, 1994;Samson, 2004 Dans le système scolaire, l'interdisciplinarité fait oeuvre d'étiquette à la mise en réseau des disciplines (Fourez, Maingain et Dufour, 2002). D'ailleurs, il existe une variété de définitions.…”
Section: Cloisonnement Disciplinaire : Un Contexte Purement Québécois?unclassified
“…En contexte scolaire, la poursuite des apprentissages s'avère essentielle, que ce soit au niveau des savoirs ou des démarches à caractère scientifique ou mathématique (Hasni, 2006). Hurley (2001) s'inscrit aussi dans ce sens avec le modèle d'intégration qu'il nomme Total integration : « Science and mathematics are taught together in intended equality » (p. 263). Ici aussi, la notion d'égalité, voire d'équité entre les deux disciplines, est présente.…”
Section: Revue Des Sciences De L'éducation De Mcgill • Vol 47 N O 2 unclassified